Ductile fracture behavior of buried X65 pipelines with defective girth welds under strike-slip fault movement - Yongxin Xu; Xingfeng Liu; Jian Zhao; Hongtu Lu; Sijian Peng; Ying Zhen; Yuguang Cao (Soil Dynamics and Earthquake Engineering, 2026)

Rebuilding the species pool within a phylogenetic framework - Sijia Yuan; Yuhao Zhao; Jean-Philippe Lessard; Thomas E. Martin; Thomas J. Matthews; Xingfeng Si (Trends in Ecology & Evolution, 2026)

Flexible tactile sensing systems: Material innovations, fabrication strategies, and intelligent applications in human-machine interfaces - Xingfeng Zhao; Yangyang Pei; Maomao He; Fangli Wang; Ting Liu; Shoujia Zhu; Xiaoyan Li; Yue Li; Bin Liu; Hongjian Zhang; Linghai Xie; Wei Huang (Chemical Engineering Journal, 2026)

Several small reservoir islands consistently support higher taxonomic, phylogenetic, functional, and interaction diversity than few large ones across multiple taxa - Yao Shen; Yuhao Zhao; Federico Riva; Wande Li; Chen Zhu; Xue Zhang; Ping Ding; Xingfeng Si (Biological Conservation, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Interpenetrating network hydrogels based on soy protein isolate and sanxan: Structure, mechanical properties, and freeze-thaw stability - Yue Zhao; Yuehan Shan; Hongjuan Wang; Zhao Zhang; Caili Wang; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Carbohydrate Polymers, 2026)

Dynamics of iron-bound organic carbon sequestration in soil-cement aggregates during the ecological restoration process - Ruzhang Gao; Bingqin Zhao; Jiwei Wang; Weihao Shi; Haoran Wang; Junhao Zhu; Xingfeng Zhang; Dong Xia; Daxiang Liu; Liming Liu; Zhenyao Xia; Wennian Xu (Journal of Environmental Chemical Engineering, 2026)

Reconceptualizing Imperfect Detection From Statistical Noise to a Lens for Ecological Signal - Yue Wang; Yuhao Zhao; Morgan W. Tingley; Xingfeng Si (Global Change Biology, 2026)

Improvement of low-oil emulsion gel performance using interfacial engineering: Impact of pea protein-curdlan interfacial structure on freeze-thaw stability and in vitro digestion - Yuehan Shan; Yue Zhao; Hongjuan Wang; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Food Chemistry, 2025)

Contrasting effects of habitat fragmentation on community stability of breeding and wintering birds in urban green spaces - Xiangxu Liu; Di Zeng; Yuhao Zhao; Shao-peng Li; Shaopeng Wang; Bicheng Li; Xiao Yuan; Shunqi Bo; Xingfeng Si (Urban Forestry & Urban Greening, 2025)

Remediation of lead-zinc-cadmium co-contaminated soil using distiller's grain biochar immobilized with Lactobacillus plantarum - Guangxu Zhu; Xingfeng Wang; Rongkun Chen; Yunyan Wang; Xingyun Zhao; Panpan Wu; Qiang Tu (Chemical Engineering Journal, 2025)

Island Biogeography and Life‐History Traits Stabilize Island Bird Communities - Yuhao Zhao; Di Zeng; Thomas J. Matthews; Dylan Craven; Morgan W. Tingley; Shaopeng Wang; Shao‐peng Li; Ping Ding; Xingfeng Si (Global Change Biology, 2025)
Islands are model systems for testing and developing ecological theories. Despite extensive research on island biodiversity, the importance of the biogeographic context for biodiversity–stability relationships is poorly understood. We addressed this knowledge gap by integrating the Equilibrium Theory of Island Biogeography (ETIB) with a functional perspective to explore island biodiversity–stability relationships. We conducted annual breeding bird surveys across 36 land‐bridge islands in eastern China over 13 years. Using this long‐term dataset, we quantified avian temporal community stability (and its components of population stability and population asynchrony) and tested how island biogeographic factors (i.e., island area, isolation, colonization rates, and extinction rates) and biodiversity facets (i.e., species richness, average population size, and life‐history traits) interact to influence stability. We found larger islands supported higher species richness due to colonization–extinction dynamics and habitat heterogeneity, which in turn promote both population stability and asynchrony. In addition, larger islands harbored larger and individually more stable populations over time. In contrast, island isolation had a weak net effect on stability, as its positive and negative influences through different pathways balanced each other out. Furthermore, species with ‘fast’ life‐history traits, characterized by shorter generation times, contributed more to community stability. These findings clarify multiple pathways through which biogeographic factors shape avian community dynamics on islands. Our study thus illustrates how island biotas maintain community stability and provides insights for preserving biodiversity and ecosystem functioning in fragmented or island‐like landscapes facing rapid biodiversity loss in an era of global change.

Seasonality, worker caste, and the interaction between island area and habitat type influence the thermal tolerance of ants on fragmented habitat islands - Yuhao Zhao; Chenxiao Wu; Chi Man Leong; Jiaxin Li; Wei Lu; Yijuan Xu; Xingfeng Si; Nathan J. Sanders (Marine Life Science & Technology, 2025)

Insights into the non-covalent interaction between muskmelon peel pectin and selected C9 aldehydes by the application of multiple spectroscopy and molecular docking - Yingying Xu; Xin Pan; Wenting Zhao; Qi Luo; Fei Lao; Xingfeng Guo; Xueli Pang; Zhijian Xiao; Jihong Wu (Food Hydrocolloids, 2025)

Architecture and stability of tripartite ecological networks with two interaction types - Yangyang Zhao; Zhicheng Zhang; Xiyang Hao; Yongjun Zhang; Xingfeng Si; Chuan Yan (Ecology, 2025)
Over the past few decades, studies on empirical ecological networks have primarily focused on single antagonistic or mutualistic interactions. However, many species engage in multiple interactions that support distinct ecosystem functions. The architecture of networks integrating these interactions, along with their cascading effects on community dynamics, remains underexplored in ecological research. In this study, we compiled two datasets of empirical plant–herbivore/host–parasitoid (PHP) and pollinator–plant–herbivore (PPH) networks, representing two common types of tripartite networks in terrestrial ecosystems: antagonism–antagonism and mutualism–antagonism. We identified the patterns of subnetwork structures and interconnection properties in these networks and examined their relationships with community stability. Our findings revealed distinct pathway effects of network architecture on persistence and local stability in both PHP and PPH networks, with subnetwork modularity and nestedness showing a few strong direct effects and mediating the indirect effects of subnetwork size and connectance. In PHP networks, subnetwork modularity enhanced persistence and local stability, whereas subnetwork nestedness directly undermined them. However, both subnetwork topologies consistently mediated the destabilizing effects of subnetwork size and connectance on the entire network. In PPH networks, persistence was primarily affected by the plant–herbivore subnetwork, while the size, connectance, and modularity of different subnetworks had opposing effects on local stability. Regarding interconnection properties, the correlation of interaction similarity destabilized PHP networks, whereas the correlation of interaction degree promoted local stability in PPH networks. Further analysis indicated that structure–persistence relationships vary significantly across guilds, and the network‐level effects of network architecture can be reversed, negligible, or biased in specific guilds. These findings advance our understanding of how network architecture influences ecosystem stability and underscore the importance of considering multiple interaction types when predicting community dynamics.

Cinnamon essential oil causes cell membrane rupture and oxidative damage of Rhizopus stolonifer to control soft rot of peaches - Zichang Zhao; Mingxia Yu; Yingying Wei; Feng Xu; Shu Jiang; Yi Chen; Phebe Ding; Xingfeng Shao (Food Control, 2025)

Hydrogen sulfide attenuates chilling injury in loquat fruit by alleviating oxidative stress and maintaining cell membrane integrity - Xinyan Shen; Yu Liu; Yuan Zeng; Yaqin Zhao; Yinqiu Bao; Xingfeng Shao; Zhengguo Wu; Yonghua Zheng; Peng Jin (Food Chemistry, 2025)

Impacts of forest restoration on multifaceted bird diversity and community assembly in the Loess Plateau of China - Dexi Zhang; Ruirui Mao; Mingxin Liu; Qian Zhou; Yizhu Wang; Xingfeng Si; Changming Zhao; Lixun Zhang (Forest Ecology and Management, 2024)

Fabrication of high internal phase emulsions (HIPEs) using pea protein isolate-hyaluronic acid-tannic acid complexes: Application of curcumin-loaded HIPEs as edible inks for 3D food printing - Zhiying Li; Liwen Zhang; Yuehan Shan; Yue Zhao; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Food Chemistry, 2024)

Influence of flavonoids from Sedum aizoon L. on mitochondrial function of Rhizopus nigricans in strawberry - Qingqing Ge; Shiyi Zhao; Xingfeng Shao; Yingying Wei; Jiahui Chen; Hongfei Wang; Feng Xu (World Journal of Microbiology and Biotechnology, 2024)

Remote sensing retrieval of aerosol types in China using geostationary satellite - Xingfeng Chen; Haonan Ding; Jiaguo Li; Lili Wang; Lei Li; Meng Xi; Limin Zhao; Zhicheng Shi; Ziyan Liu (Atmospheric Research, 2024)

Island biogeography of soundscapes: Island area shapes spatial patterns of avian acoustic diversity - Peng Han; Yuhao Zhao; Yi Kang; Ping Ding; Xingfeng Si (Journal of Biogeography, 2024)
Aim The equilibrium theory of island biogeography predicts the positive species–area relationship and the negative species–isolation relationship, resulting in higher species richness on large and close islands. Unlike species richness, soundscape diversity integrates sound from various sources (e.g. biophony, geophony and anthrophony). However, how soundscape diversity varies with island area and isolation still needs to be tested. Here, we explored the island biogeography of bird soundscapes and the determinants of island attributes in shaping bird diversity and soundscape diversity. Location Thousand Island Lake, Zhejiang, China. Taxon Birds. Methods We recorded avian soundscapes by audio recorders and censused bird diversity by line transects on 20 land‐bridge islands. We calculated four acoustic indices (acoustic complexity index, bioacoustic index, acoustic evenness index and acoustic entropy index) to assess acoustic richness, evenness and heterogeneity to explore the soundscape diversity of birds. We used multiple linear regressions, spatial autoregressions and piecewise structural equation models to examine the relationships between bird richness and acoustic diversity, and island attributes. Results We found positive diversity–area relationships for avian soundscapes. Larger islands had more vocal species and higher habitat diversity, which led to an increment in the richness and unevenness of avian soundscapes on large islands. Acoustic evenness decreased with increasing isolation (distance to the mainland). Main Conclusions Soundscapes on large islands are more diverse than those on small islands. Rich acoustic assemblages and heterogeneous habitats promote increased soundscape diversity on islands. Conversely, the lack of vocal contributors, resulting in a decrement in the communication of acoustic signals, can create a lower soundscape diversity on small and remote islands. Our study emphasizes the necessity of examining both species and habitat diversity in island biogeography for better understanding the underlying mechanisms determining biological soundscapes on islands.

Transcriptomic analysis reveals the resistance mechanism of flavonoids from Sedum aizoon L. to Rhizopus nigricans in postharvest strawberry fruit - Qingqing Ge; Shiyi Zhao; Xingfeng Shao; Yingying Wei; Jiahui Chen; Hongfei Wang; Feng Xu (Postharvest Biology and Technology, 2024)

Uncovering widespread Anthropocene dietary shifts in Chinese large mammalian herbivores - Yangheshan Yang; Yuhao Zhao; Thomas A. Stidham; Xiangxu Liu; Xichao Zhu; Bicheng Li; Lixun Zhang; Xijun Ni; Xingfeng Si (Ecology Letters, 2024)
The Anthropocene's human‐dominated habitat expansion endangers global biodiversity. However, large mammalian herbivores experienced few extinctions during the 20th century, hinting at potentially overlooked ecological responses of a group sensitive to global change. Using dental microwear as a proxy, we studied large herbivore dietary niches over a century across mainland China before (1880s–1910s) and after (1970s–1990s) the human population explosion. We uncovered widespread and significant shifts (interspecific microwear differences increased and intraspecific microwear dispersion expanded) within dietary niches linked to geographical areas with rapid industrialization and population growth in eastern China. By contrast, in western China, where human population growth was slower, we found no indications of shifts in herbivore dietary niches. Further regression analysis links the intensity of microwear changes to human land‐use expansion. These analyses highlight dietary adjustments of large herbivores as a likely key factor in their adaptation across a century of large‐scale human‐driven changes.

Characterizing bird species for achieving the win-wins of conserving biodiversity and enhancing regulating ecosystem services in urban green spaces - Xiangxu Liu; Yuhao Zhao; Di Zeng; Yangheshan Yang; Wande Li; Yi Kang; Guangpeng Wei; Xiao Yuan; Shunqi Bo; Xingfeng Si (Urban Forestry & Urban Greening, 2023)

Heterogeneous Fenton system driven by iron-loaded sludge biochar for sulfamethoxazole-containing wastewater treatment - Liheng Liu; Ronghao Yu; Shixiong Zhao; Xingfeng Cao; Xuehong Zhang; Shaoyuan Bai (Journal of Environmental Management, 2023)

Island area, not isolation, drives taxonomic, phylogenetic and functional diversity of ants on land‐bridge islands - Yuhao Zhao; Robert R. Dunn; Haonan Zhou; Xingfeng Si; Ping Ding (Journal of Biogeography, 2020)
Aim To explore the impact of island area and isolation on multiple dimensions of ant biodiversity (taxonomic, phylogenetic and functional diversity) and the underlying processes of community assembly on islands. Location Thousand Island Lake, Zhejiang, China, created by dam construction in 1959. Taxon Ants. Methods We sampled ants on 33 islands, built a species‐level phylogenetic tree and measured five morphological traits of all species collected to estimate taxonomic, phylogenetic and functional diversity. We used multiple linear regression models and null models to examine the relationships between diversity metrics and island variables (area and isolation). Results We recorded 97 ant species on the study islands. We verified positive diversity–area relationships for species richness, phylogenetic diversity and functional diversity. However, although functional and phylogenetic community structure were indistinguishable from random communities, phylogenetic structure tended to be clustered, whereas functional structure tended to be overdispersed. Additionally, we found the structure of ant communities shifted from phylogenetic and functional clustering on smaller islands to phylogenetic and functional overdispersion on larger islands. Main conclusions Our results support the hypothesis that environmental filtering is the dominant process structuring ant communities on smaller islands, and that competitive exclusion becomes more important on larger islands. Thus, island area acts as an important filter even though ant community structure on the study islands was indistinguishable from random communities. Moreover, our results show that environmental filtering influences phylogenetic community structure of ants, whereas competitive exclusion influences functional community structure of ants. These findings highlight the need to examine both phylogenetic and functional diversity in order to understand the mechanisms that govern the assembly of natural communities on islands.

A transcriptome analysis of the antibacterial mechanism of flavonoids from Sedum aizoon L. against Shewanella putrefaciens - Jing Wang; Zongyu Chi; Ke Zhao; Hongfei Wang; Xin Zhang; Feng Xu; Xingfeng Shao; Yingying Wei (World Journal of Microbiology and Biotechnology, 2020)

QTL for flag leaf size and their influence on yield-related traits in wheat - Chunhua Zhao; Yinguang Bao; Xiuqin Wang; Haitao Yu; Anming Ding; Chunhui Guan; Junpeng Cui; Yongzhen Wu; Han Sun; Xingfeng Li; Dongfeng Zhai; Linzhi Li; et al. (Euphytica, 2018)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

Construction of an integrative linkage map and QTL mapping of grain yield-related traits using three related wheat RIL populations - Fa Cui; Chunhua Zhao; Anming Ding; Jun Li; Lin Wang; Xingfeng Li; Yinguang Bao; Junming Li; Honggang Wang (Theoretical and Applied Genetics, 2014)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

Wheat kernel dimensions: how do they contribute to kernel weight at an individual QTL level? - FA CUI; ANMING DING; JUN LI; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; XIUQIN WANG; LIN WANG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

Development and characterization of microsatellite loci for Rosa odorata var. gigantea Rehder & E. H. Wilson (Rosaceae) - Jing Meng; Dezhu Li; Tingshuang Yi; Junbo Yang; Xingfeng Zhao (Conservation Genetics, 2009)